2016
DOI: 10.1016/j.drugalcdep.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year study of factors associated with alcohol treatment use and non-use in a U.S. population sample

Abstract: Background This study seeks to identify changes in perceived barriers to alcohol treatment and predictors of treatment use between 1991–92 and 2001–02, to potentially help understand reported reductions in treatment use at this time. Social, economic, and health trends during these 10 years provide a context for the study. Methods Subjects were Whites, Blacks, and Hispanics. The data were from the National Longitudinal Alcohol Epidemiologic Survey (NLAES) and the National Epidemiologic Survey on Alcohol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 32 publications
5
36
0
Order By: Relevance
“…Consistent with the alcohol (Chartier et al, 2016; Grant, 1995; Perron et al, 2009) and cannabis (Khan et al, 2013) literatures, enabling factors most frequently endorsed among individuals with lifetime cannabis use disorder included inability to pay for services and several logistical/structural issues (e.g., time, transportation). Financial and logistical/structural barriers may be more amenable to change in the short-term (e.g., through policy interventions that increase access to insurance or transportation) than changes aimed at altering attitudes and beliefs, especially those aimed at stigma.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Consistent with the alcohol (Chartier et al, 2016; Grant, 1995; Perron et al, 2009) and cannabis (Khan et al, 2013) literatures, enabling factors most frequently endorsed among individuals with lifetime cannabis use disorder included inability to pay for services and several logistical/structural issues (e.g., time, transportation). Financial and logistical/structural barriers may be more amenable to change in the short-term (e.g., through policy interventions that increase access to insurance or transportation) than changes aimed at altering attitudes and beliefs, especially those aimed at stigma.…”
Section: Discussionmentioning
confidence: 78%
“…However, these prior studies also showed that predisposing and enabling factors (e.g., income, education) impact treatment utilization for alcohol and other drug use disorders (Chartier et al, 2016; Grella et al, 2009; Grant, 1996). An important premise of the behavioral model underlying the organizational framework of this study is the public policy concept of equitable distribution– that is, treatment services should be distributed solely on the basis of treatment need9 (Andersen, 2008; Andersen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Older individuals are more likely to have endorsed utilizing services than those under the age of 45, which may reflect age‐related reporting biases and longer duration of AUD and time to recognize problems and seek treatment, or it may also reflect reduced attention to AUDs in younger cohorts (Alvanzo et al, ). Past‐year estimates of treatment utilization vary by study and range from less than 10% (Chartier et al, ) to over 20% (Evans‐Polce and Schuler, ). Of note is the fact that past‐year estimates were assessed in the 1990s (Chartier et al, ), early 2000s (Chartier et al, ), and early 2010s (Evans‐Polce and Schuler, ) which may reflect natural generational or other sample differences (see below).…”
Section: Service Use For Alcohol Problemsmentioning
confidence: 99%
“…However, unless directly addressed, barriers such as addiction stigma will continue to impede quality of care and utilization of services (Grant et al, 2016, 2015; Volkow, 2008). Critically, a 10-year-long epidemiological survey suggests that addiction stigma has remained stable over time in the U.S. (Chartier et al, 2016; Pescosolido et al, 2010). Simultaneously, addiction stigma continues to be understudied and poorly understood (Kulesza et al, 2013; Livingston et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the individual-level, persons with SUDs might decide against seeking help to avoid anticipated stigma from healthcare providers, employers, and/or neighbors (Link et al, 2001, 1989). Longitudinal (Chartier et al, 2016) and cross-sectional data (Keyes et al, 2010; Oleski et al, 2010; Radcliffe and Stevens, 2008) indicate that individuals, who perceive high levels of addiction stigma within society, are less likely to access SUDs help and treatment services.…”
Section: Introductionmentioning
confidence: 99%